Knowledge translation: The missing link to improving the quality of health care - Michael, Rene; Della, Phillip (Cambridge Publishing, 2013)
The importance of transferring knowledge from research into health care policy and practice is widely recognised. A major problem, however, is the complexity of the process which policymakers, managers, clinicians and researchers struggle with. This can result in research findings not being used, with subsequent wasted resources and the inability to provide treatments to those who need them. Through knowledge translation and collaboration between researchers and users of research, we can position the way to address the problem of the underutilisation of research findings, which leads to quality and safety in patient care. This article presents a discussion about the translation of knowledge into practice.